Bioelectromagnetic healing : a rationale for its use - Valone, Thomas F. (Integrity Research Institute, 2003)
Author, Scientist, and former U.S. Patent Engineer, Dr. Tom Valone has taken on the extremely difficult task of organizing and explaining the array of alternative medical technologies which have been developed over the years. Many of the fascinating devices described and scientifically documented were remarkably successful in curing otherwise terminal medical conditions such as cancer. Because they operated outside the boundaries of the scientific and medical paradigms of the times, the remarkable healing effectiveness of these pioneering technologies were often disavowed by the medical author.